Fibreboard from coconut husk a plant design - Gemanil, Edith; Gonzalez, Lea.; Lim, Chi Ko. (Diliman, Quezon City College of Engineering, 1972)
Plant: Fibreboard plant -- Site: Lucena, Quezon -- Raw material: coconut dust from coconut husk -- Product: fibreboard -- Working days: 300 days/year -- Plant capacity: 37,800 metric tons -- Total capital investment: 6,322,023.00 -- Manufacturing cost: 1,580,505.00 -- Annual sales at maximum production: 20,832,000.00 -- Profit before taxes: 13.396,350.00 -- Break even point: 0.75 -- Pay-out time: 1.165 years
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Fiberboard industry; Particle board; Fiberboard